Unanticipated gains : origins of network inequality in everyday life - Small, Mario Luis. (New York ; Oxford : Oxford University Press, 2009)
Why do some people have better social networks than others? This book argues that the answer lies less in people's deliberate 'networking' than in the institutional conditions of the colleges, firms, gyms, and other organizations in which they happen to participate routinely.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Social networks; Social capital (Sociology); Day care centers -- Case studies